Maternidade e academia: políticas de inclusão de gênero na academia - Almeida, Camila Infanger (2020)
In the discussion aimed at promoting the inclusion of women in academia, the phenomenon of under-representation of women in senior academic positions is central. Importantly, academic mothers are in an even more vulnerable position within an environment where researchers with career paths marked by breaks, face disadvantages, regardless of their scientific potential. (Stobbe et al., 2004; Valian, 1998). The research that produced this dissertation questioned the effectiveness of existing organizational and political practices towards the inclusion of gender in academia, regarding the needs of the academic mothers. The dissertation macro objective was to address the topic of academic career for academic mothers under the framework of the permanence of women in science, through the analysis of gender inclusion policies that had motherhood as an anchor of their designs. Therefore, the specific objectives aim at (i) through a literature review to map and identify the nuances of scientific production on the terms ‘Motherhood’ and ‘Academia’; (ii) through a case study, analyze the influences on the flow of the maternity leave benefit offered by an important science funding agency in Brazil and, finally, (iii) through a co-variational study, verify the potential relationship between the elements 'support' and 'productivity' among the academic mothers. The findings revealed that (i) the literature produced on this topic theme is authored exclusively by women, predominantly from developed countries, yet with low intersectionality with other areas and with theories in a position clearly opposed to neoliberal thinking and related productivist culture; (ii) despite the existence of the maternity leave policy, there remains a resistance in academic institutions and within the academic community for academic mothers to benefit effectively from the policy and (iii) there is a co-variation between the elements ‘support ' and 'productivity '. Notably, the family, governmental and institutional spheres must work in a combined manner, in order to provide adequate conditions for academic mothers to be able to produce in the same way as men and childless researchers do.